IDEOLOGI DAN AQIDAH ASWAJA AN NAHDLIYAH - Ahmad Bukhori (Jurnal Studi Pesantren, 2023)
The understanding of ahlus sunnah wa al-jama'ah in nahdlatul ulama includes aspects of aqidah, sharia and morals. All three are a unified teaching that covers all aspects of Islamic religious principles. Based on the Asy'ariyah and maturidiyah manhaj (thought patterns) in the field of aqidah, the four major madzah imams in the field of fiqh (Imam Hanafi, Maliki, Shafi'I and Hambali), and in the field of tasawuf adhere to the manhaj of Imam al-Ghazali and Imam Abu al -Qasim al-Junaidi al-Baghdadi, as well as other imams who are in line with Islamic sharia. The main characteristics of Aswaja NU are the attitude of tawassuth and I'tidal (middle and/or balance). That is, always balance in using arguments, between naqli arguments and aqli arguments, between Jabariyah and Qadariyah opinions and a moderate attitude in addressing dunyawiyah. In matters of fiqh, the middle attitude between "ijtihad" and taqlid is blind. Namely by way of bermazhab. The characteristic of this attitude is firmness in matters that are qath'iyyat and tolerant in matters of zhanniyyat. Ahlussunnah wal al-jama'ah Islam is the teachings that the Prophet Muhammad conveyed to his friends and he practiced and practiced his friends. Indeed, there are those who consider the hadith to contain weaknesses. However, if it is used as a guideline and guideline for measuring views and behavior that can be justified by Islamic teachings, it will definitely be better than the testimony of experts whose strength and truth are uncertain. Kata Kunci: Ideology, Aswaja an-Nahdliyah